Detection of EXP1-Specific CD4+ T Cell Responses Directed Against a Broad Range of Epitopes Including Two Promiscuous MHC Class II Binders During Acute Plasmodium falciparum Malaria - Heide, Janna; Wildner, Nils H.; Ackermann, Christin; Wittner, Melanie; Marget, Matthias; Sette, Alessandro; Sidney, John; Jacobs, Thomas; Schulze zur Wiesch, Julian (Frontiers in Immunology, 2020)
BACKGROUND: T cells are thought to play a major role in conferring immunity against malaria. This study aimed to comprehensively define the breadth and specificity of the Plasmodium falciparum (P. falciparum)-specific CD4+ T cell response directed against the exported protein 1 (EXP1) in a cohort of patients diagnosed with acute malaria. METHODS: Peripheral blood mononuclear cells of 44 patients acutely infected with P. falciparum, and of one patient infected with P. vivax, were stimulated and cultured in vitro with an overlapping set of 31 P. falciparum-specific 13-17-mer peptides covering the entire EXP1 sequence. EXP1-specific T cell responses were analyzed by ELISPOT and intracellular cytokine staining for interferon-γ production after re-stimulation with individual peptides. For further characterization of the epitopes, in silico and in vitro human leukocyte antigen (HLA) binding studies and fine mapping assays were performed. RESULTS: We detected one or more EXP1-specific CD4+ T cell responses (mean: 1.09, range 0-5) in 47% (21/45) of our patients. Responses were directed against 15 of the 31 EXP1 peptides. Peptides EXP1-P13 (aa60-74) and P15 (aa70-85) were detected by 18% (n=8) and 27% (n=12) of the 45 patients screened. The optimal length, as well as the corresponding most likely HLA-restriction, of each of these two peptides was assessed. Interestingly, we also identified one CD4+ T cell response against peptide EXP1-P15 in a patient who was infected with P. vivax but not falciparum. CONCLUSIONS: This first detailed characterization of novel EXP1-specific T cell epitopes provides important information for future analysis with major histocompatibility complex-multimer technology as well as for immunomonitoring and vaccine design.